The influence of online consumer reviews on purchase intention among young adults - Osman, Syuhaily; Lim, Hui Ying (Universal Publishers, 2022)
Purpose: In today’s world,social media has brought large impacts to the consumers’ lifestyle as consumers spent most of their time in surfing and browsing them to get information. Hence, online consumer reviews will direct consumers to choose their matching products from variety of products available. This study is to ascertain the influence of online consumer reviews on the purchase intention among young adults, particularly concentrating on the level of source credibility, review volume and review valence. Design/methodology/approach: Elaboration Likelihood Model (ELM) is the theory that applied in this study since it comprehends in what way the online consumer reviews persuades other consumers. The population of this study was young adults in Batu Pahat with the sample size of 200 respondents selected by using simple random sampling method. Findings: The results from multiple regression analysis showed that all the three independent variables were the significant predictors to the purchase intention of online consumer reviews in which review valence was the strongest predictor (B = 0.574; p<0.005). Research limitations/implications: This study demonstrated the influence of online consumer reviews by clarifying 49.80% of the coefficient of determination on the purchase intention thereby adding credit to the existing ELM theory. Practical implications: The finding implied that marketers should take the opportunity to develop new market tactic and improve their way of business, services and product quality in order to increase positive reviews in online platform. Originality/value: Given the paramount importance of peripheral cues in shaping consumers’ perceptions of online review, this study focused on the influences online consumer reviews by using peripheral cues in ELM theory on consumers’ purchase intention.